Aktualna politična situacija med pripadniki slovenske skupnosti na Hrvaškem - Riman, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article offers an analysis of the status of the members of the Slovene community in Croatia with special focus on their participation in public political life. Their inclusion into public political life is highly important for the status of the minority. Slovenes in Croatia are well known to be apolitical, refusing to publicly identify themselves as members of the Slovene minority. Their lack of activity in politics contributes to their less favourable status, manifested above all in the acquisition of certain rights.
Keywords: Hrvaška; manjšinska politika; manjšinsko predstavništvo; politična participacija; slovenska manjšina